PENGARUH MOTIVASI DAN MINAT BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 8 KOTA JAMBI - Deasriza Indah Sari; Kasiono Kasiono (SJEE (Scientific Journals of Economic Education), 2020)
This study aims to determine the motivation and interest in learning towards student learning outcomes in economic subjects in class X SMA Negeri 8 Jambi City. This research design uses quantitative methods. The number of population in this study were 140 students of class X. The data used were primary and secondary data with data collection techniques through distributing questionnaires (questionnaires). Based on the simple regression average values, the mean value of students can be seen that interest and motivation on learning outcomes have an influence of 4.28%, so that the value is categorized as still lacking. After being examined through research, the aspects that show the student's score are lacking, due to the wrong choice of majors, so that interest and motivation to learn accounting is still classified as lacking.